2018
DOI: 10.1098/rspb.2018.1237
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mice exposed to a high-fat diet in utero influence the behaviour of their nursing dam

Abstract: The behaviour of a nursing dam influences the development, physiology, and behaviour of her offspring. Maternal behaviours can be modulated both by environmental factors, including diet, and by physical or behavioural characteristics of the offspring. In most studies of the effects of the environment on maternal behaviour, F 0 dams nurse their own F 1 offspring. Because the F 1 are indirectly exposed to the environmental stressor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[ 39 ] However, in a previous study exploiting the same cross‐fostering model described here, we demonstrated that maternal diet had no direct effect on care behavior, and that maternal care was predominantly driven by the in utero environment experienced by the F1 offspring. [ 40 ] Given that Ct‐MetS mice presenting with NAFLD were born to Ct dams and therefore did not experience an adverse in utero environment, we do not expect maternal behavior to be a significant mechanism in the observed programming of NAFLD. Further studies will be required to determine the nature of the signal that activates Zac1 expression in the F1 liver.…”
Section: Discussionmentioning
confidence: 99%
“…[ 39 ] However, in a previous study exploiting the same cross‐fostering model described here, we demonstrated that maternal diet had no direct effect on care behavior, and that maternal care was predominantly driven by the in utero environment experienced by the F1 offspring. [ 40 ] Given that Ct‐MetS mice presenting with NAFLD were born to Ct dams and therefore did not experience an adverse in utero environment, we do not expect maternal behavior to be a significant mechanism in the observed programming of NAFLD. Further studies will be required to determine the nature of the signal that activates Zac1 expression in the F1 liver.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence from another study suggests that an obese phenotype (significant weight gain) rather than high-fat diet exposure alone is required to adversely impact offspring neurodevelopment and behaviour [ 13 ]. A third study [ 14 ] using inbred mice showed that the dams of neonatal mice exposed to a high-fat diet in utero were less interactive than neonates exposed to a control diet. Using a cross-fostering design, this was demonstrated to be independent of the mothers’ diet, instead suggesting a role of offspring physiological changes that cue maternal interaction with pups.…”
Section: Maternal Factors Influencing Offspring Neurodevelopment and ...mentioning
confidence: 99%
“…HFD consumption during pre- and post-partum periods, two metabolically challenging periods, produced mixed changes in the gestational body weight, but generally increased adiposity and induced hyperleptinemia in dams (see Supplementary Table S1 ). The behavioural profile of the dams showed that maternal HFD had a negative impact on maternal behaviour, especially regarding nest building and pup licking/grooming [ 80 , 81 ].…”
Section: Impact Of a High-fat Diet Treatment On Emotionality Cognitio...mentioning
confidence: 99%